2019
DOI: 10.1186/s12885-019-5467-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment preferences of patients with relapsed and refractory multiple myeloma: a qualitative study

Abstract: BackgroundMultiple myeloma is a haematological malignancy characterized by significant morbidity and mortality. This study sought to develop an in-depth understanding of patients’ lived experiences of relapsed or refractory multiple myeloma (RRMM) and its treatment, and to identify which features of treatment were most important to them.MethodsQualitative interviews and focus groups (FGs) were conducted with 32 people living with RRMM across Canada. In Phase 1, interviews focused on participants’ accounts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 33 publications
10
54
0
Order By: Relevance
“…As in previous studies, patients reported high symptom burden, including symptoms associated with HRQoL [1,2,4,5,7,9]. In agreement with another qualitative study on treatment preferences in MM [3], symptoms such as fatigue and bone pain, and side effects such as gastrointestinal symptoms and peripheral neuropathy, were the most frequently discussed by patients as significantly disruptive to HRQoL.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in previous studies, patients reported high symptom burden, including symptoms associated with HRQoL [1,2,4,5,7,9]. In agreement with another qualitative study on treatment preferences in MM [3], symptoms such as fatigue and bone pain, and side effects such as gastrointestinal symptoms and peripheral neuropathy, were the most frequently discussed by patients as significantly disruptive to HRQoL.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple myeloma (MM) is the second most common hematological cancer and is characterized by high levels of mortality [1][2][3][4]. Despite recent treatment advances, MM remains incurable [1][2][3][5][6][7][8] and becomes harder to treat over time [2,3,8]. Development of new treatment options, particularly those that can be tolerated over the long term, is an ongoing priority.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the MDASI-MM and the EORTC-QLQ-MY20, the MyPOS contains more items regarding worry about the future, information needs, and coping processes as well as adaptation processes, all relevant to and reflecting the prolonged disease trajectory. These issues have also been highlighted as important in recent qualitative studies focusing on the advanced myeloma population [11][12][13]57,58]. The MyPOS was developed as a tool to go beyond the simple assessment of symptom status and asking for an evaluation of physical, emotional, spiritual, and QoL morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the MDASI-MM and the EORTC-QLQ-MY20, the MyPOS contains more items regarding worry about the future, information needs, and coping processes as well as adaptation processes, all relevant to and reflecting the prolonged disease trajectory. These issues have been also highlighted as important in recent qualitative studies focusing on the advanced myeloma population [11][12][13]57,58]. The MyPOS was developed as a tool to go beyond the simple assessment of symptom status and asking for an evaluation of physical, emotional, spiritual, and QoL morbidity.…”
Section: Discussionmentioning
confidence: 99%